1989
DOI: 10.1103/physrevlett.63.271
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale resonant modification of the polar ionosphere by electromagnetic waves

Abstract: Large-scale density modification was optimally achieved by electromagnetic waves whose frequency matched the plasma frequency at a height where the ionospheric density profile was flat. The density in this region was dramatically clamped during the morning when it normally increases from solar ionization. Electromagnetic wave propagation in the polar magnetic field geometry and strongly resonantly enhanced electrostatic fields over a large region of constant density account for the observation.PACS 52.25.Sw, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Large‐scale electron density modifications have been observed at auroral latitudes in experiments at the HIPAS facility during conditions when the pump frequency was near the maximum ionospheric plasma frequency (critical frequency) where the vertical gradient in the density profile is nearly zero [ Wong et al , 1989]. The experiments were conducted during mornings when the ionospheric plasma density normally slowly increases as a result of the increasing ionizing solar radiation.…”
Section: F Region Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large‐scale electron density modifications have been observed at auroral latitudes in experiments at the HIPAS facility during conditions when the pump frequency was near the maximum ionospheric plasma frequency (critical frequency) where the vertical gradient in the density profile is nearly zero [ Wong et al , 1989]. The experiments were conducted during mornings when the ionospheric plasma density normally slowly increases as a result of the increasing ionizing solar radiation.…”
Section: F Region Propertiesmentioning
confidence: 99%
“…The experimental results for pumping near the critical frequency were compared to particle‐in‐cell simulations [ Wong et al , 1989]. The simulations showed that after about 150 electron plasma periods, multiple density cavitons of roughly 10% depth had formed.…”
Section: F Region Propertiesmentioning
confidence: 99%
“…When the pump frequency (--2.85 MHz) matches plasma frequency at the bottom of the F layer, the electric field has been resonantly enhanced and a strong interaction takes place [Wong et al, 1989].…”
Section: Introductionmentioning
confidence: 99%
“…Since the power of seven antennas at the center of the heating region is about three times stronger than that of four antemlas, it is expected that the density modulation in the 1-7 configuration will be more pronounced than that of the 4-4 configuration. A larger density modulation at the resonance height has been observed at HIPAS when all eight transmitters were turned on [Wong et al, 1989].…”
Section: Introductionmentioning
confidence: 99%